‘I’m a red-blooded male’: Understanding men’s experiences of domestic abuse through a feminist lens - Westmarland, Nicole (Criminology & criminal justice, 2025)
The ways in which gendered expectations of women are used to maintain power and control by male perpetrators of domestic abuse are now well understood. It is also increasingly recognised that men can be victims of domestic abuse. This has led to calls to de-gender theories of violence and abuse, and arguments that the feminist theories which underpin many interventions are outdated. We draw on the experiences of 344 men using a helpline for male victim–survivors of domestic abuse to show that patriarchal constructions of relationships, femininity and masculinity, which underpin women’s experiences of domestic abuse by men are also central to understanding men’s experiences of domestic abuse by women. We propose that men’s victimisation by women perpetrators is not incompatible with feminist understandings of domestic abuse. Rather, that the influence of patriarchal norms in men’s victimisation accentuates the importance of gender in understanding and responding to domestic abuse.